Chromen Derivatives: A Detailed Experimental and Theoretical Investigation as Corrosion Inhibitors For Mild Steel in HCL 1M - A. Larioui; I. Chaouki; F. Hamouche; A. El Amri; N. Errahmany; F. El Hajri; S. El Hamzi; N. Dkhireche; S. El Bakkali; S. Boukhris (Materials Research, 2025)
Corrosion of metals poses a significant threat to the economy, environment, and public health due to its harmful effects and the production of contaminated materials. Corrosion inhibitors are crucial in protecting metallic substances, especially in harsh environments. This research investigated the corrosion inhibitory properties of two novel chromen-6-one (BCC) derivatives named BBC-4-Cl and BBC-4-CH3 in 1 M hydrochloric acid solution. The electrochemical characteristics of these two heterocyclic compounds were evaluated using electrochemical tests, SEM and EDX surface characterization analyses, and theoretical studies using a multiscale computational approach (including DFT, MCS, FFV, and RDF). The electrochemical data revealed that BBC-4-Cl and BBC-4-CH3 acted as mixed-type corrosion inhibitors. We found that the effectiveness of these inhibitors was directly proportional to their concentration, with higher concentrations leading to a significant increase in effectiveness. This was reflected in a reduction in corrosion current and increased polarization resistance. The effectiveness reached 76% and 89% at 298 K in 10-3 M BCC-4-Cl and BCC-4-CH3, respectively. The results suggested a strong adsorption of the molecules on the surface indicating a chemisorption process. Surface analyses confirmed the formation of a protective layer on the steel surface, and the theoretical study confirmed these results.